Doubling for general sets - Buckley, Stephen M.; Hanson, Bruce; MacManus, Paul (MATHEMATICA SCANDINAVICA, 2001)
We investigate doubling conditions defined in terms of measurable bounded sets and find a simple characterization of quasisymmetrically thick Cantor sets on the line.